Adoption Costs Associated With Processing Strengths and Weaknesses Methods for Learning Disabilities Identification - Williams, Jacob (Sch Psychol Forum Res Pract, 2018)
There is controversy regarding the relative merits of cognitive assessment for the identification of learning disabilities. Proponents of cognitive assessment have suggested that multitiered systems of support (MTSS) should be supplemented with routine, systematic assessment of cognitive processes following a determination of inadequate response to evidence-based interventions in order to document a pattern of processing strengths and weaknesses (PSW methods) as an inclusionary criterion for learning disabilities. However, the financial costs incurred by this addition to MTSS are not well known. In the present study, we present a systematic case study to estimate the costs associated with adopting routine assessment of cognitive processing for students referred for special education evaluation. We estimate that implementation within a district would cost between $1,960 and $2,400 per student, assuming no existing infrastructure. These expenses are discussed in relation to evidence for the educational value of such assessments and inherent trade-offs between assessment and intervention.